The Effect of Interactive Learning Media on Learning Outcomes and Motivation of Grade 5 Students in Science Subjects - Dinda Rizka Maulidya; Tri Astuti (Jurnal Penelitian Pendidikan IPA, 2025)
This study was conducted with the aim of analyzing and testing the influence of interactive learning media on science learning outcomes and the influence of interactive learning media on students' learning motivation. The interactive media in question is Microsoft Power Point media. This study uses a quantitative method with an ex post facto approach. The population taken was from four schools, namely SDI Miftahul Hikmah, SDIT Permata, SDN Sooko 1 and SDN Gayaman. Based on the results of observations, the four schools have implemented interactive learning media and have the same accreditation and facilities. The research sample was taken from class V with a total of 167 students. The data collection technique used a questionnaire method, a method of documenting students' semester science scores and an interview method for the initial study. The data analysis technique used simple regression analysis. The results of the analysis showed that the Interactive Learning variable (X) had a significant influence on Learning Outcomes (Y1) with a sig value of 0.000 <0.05, R Square of 70.50%, and an F test of 0.000 <0.05; The Interactive Learning variable (X) has an influence on Learning Motivation (Y2) with a mean value of 89.2, a median of 90, where the KKM value for each school is 70.